Distracted Driving Measurement for Manual Destination Entry Using Navigation Device - Mohd Siam, M.F.; Ab Rashid, A.A.; Ibrahim, M.K.A.; Borhan, N. (Journal of the Society of Automotive Engineers Malaysia, 2021)
This paper discusses the measurement of driver distraction for manual destination entry using navigation devices in a simulated traffic environment. 46 participants completed a number of secondary tasks while synchronously conducting the driving activities and performing the detection task. For comparison of the driving scenarios, three scenarios were used which were low speed, high speed, and traffic congestion. Secondary tasks including 0, 1, 2, 3, 4, 5, 7, 9, 14, 20 number of characters were assessed in the study. The results of this study showed that participants were more distracted with more demanding tasks to handle the destination entry as compared to baseline. In addition, we also found that participants attended the worst in terms of higher RT in traffic jam scenarios as compared to other two scenarios. This study shows that doing navigation task specifically destination entry while driving is considered as a distracting activity that possibly elevates the risk of a crash.